Training of ultra-fast speech comprehension induces functional reorganization of the central-visual system in late-blind humans - Dietrich, Susanne; Hertrich, Ingo; Ackermann, Hermann (Frontiers in Human Neuroscience, 2013)
Individuals suffering from vision loss of a peripheral origin may learn to understand spoken language at a rate of up to about 22 syllables (syl) per seconds (s) – exceeding by far the maximum performance level of untrained listeners (ca. 8 syl/s). Previous findings indicate the central-visual system to contribute to the processing of accelerated speech in blind subjects. As an extension, the present training study addresses the issue whether acquisition of ultra-fast (18 syl/s) speech perception skills induces de novo central-visual hemodynamic activation in late-blind participants. Furthermore, we asked to what extent subjects with normal or residual vision can improve understanding of accelerated verbal utterances by means of specific training measures. To these ends, functional magnetic resonance imaging (fMRI) was performed while subjects were listening to forward and reversed sentence utterances of moderately fast and ultra-fast syllable rates (8 or 18 syl/s) prior to and after a training period of ca. six months. Four of six participants showed – independently from residual visual functions – considerable enhancement of ultra-fast speech perception (about 70 percentage points correctly repeated words) whereas behavioral performance did not change in the two remaining participants. Only subjects with very low visual acuity displayed training-induced hemodynamic activation of the central-visual system. By contrast, participants with moderately impaired or even normal visual acuity showed, instead, increased right-hemispheric frontal or bilateral anterior temporal lobe responses after training. All subjects with significant training effects displayed a concomitant increase of hemodynamic activation of left-hemispheric SMA. In spite of similar behavioral performance, trained “experts” appear to use distinct strategies of ultra-fast speech processing depending on whether the occipital cortex is still deployed for visual processing.